(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the rapidly growing digital age, student leadership is taking on new forms based on technological innovations and digital platforms. This article explores how students use social media, coding, and digital tools to anage initiatives, address Real-world issues, and bring social change to their communities. It presents case studies, research results and expert insights, highlighting how digital leadership gives young people the opportunity to make proactive changes. With more and more access to technology, students around the world prove that leadership is no longer limited to traditional settings, but develops on the internet, breaking down barriers and building bridges for a more inclusive and dynamic future.